2003
DOI: 10.1042/bst0311010
|View full text |Cite
|
Sign up to set email alerts
|

The development of chromatography for the characterization of protein interactions: a personal perspective

Abstract: This article reviews the progress of a personal endeavour to develop chromatography as a quantitative procedure for the determination of reaction stoichiometries and equilibrium constants governing protein interactions. As well as affording insight into an aspect of chromatography with which many protein chemists are unfamiliar, it shows the way in which minor adaptations of conventional chromatographic practices have rendered the technique one of the most powerful methods available for the characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Indeed, the c(s) distributions can exhibit broadening for other reasons. Nevertheless, just as our analysis of the difference curves by incorporating kinetics, so too can the gel filtration elution profiles for ClpB be analyzed by incorporating kinetic parameters . However, to our knowledge, this analysis has not been applied to the examination of ClpB using gel filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the c(s) distributions can exhibit broadening for other reasons. Nevertheless, just as our analysis of the difference curves by incorporating kinetics, so too can the gel filtration elution profiles for ClpB be analyzed by incorporating kinetic parameters . However, to our knowledge, this analysis has not been applied to the examination of ClpB using gel filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Frontal analysis using soluble proteins Another common technique for examining drug-protein interactions in solution is frontal analysis. 7,[45][46][47][48][49][50][51] This approach was first employed in 1964-1965 with soluble agents to examine protein-protein binding 45 and drug-protein interactions 46 and is still an important method for such measurements. Frontal analysis using soluble proteins is different from the zonal elution methods described in the previous section because a large volume of a drug/protein mixture is used instead of a small plug of sample.…”
Section: Zonal Elution Methods Using Soluble Proteinsmentioning
confidence: 99%
“…Various chromatography based techniques have emerged in the last years in order to characterize protein-protein interactions [17,[26][27][28][29][30][31]. For examples, Stevens [32] proposed the use of small-zone size exclusion chromatography for investigating protein-protein association and Wen et al [33] showed the benefit of the additional combination of various detection methods for analyzing protein-protein interaction (see also [17]).…”
mentioning
confidence: 99%